Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II Section XII Miscellaneous - Planning Commission (Planning Commission, 1985)
During 1982- 83, Government sanctioned a scheme viz., strengthening of Planning Machinery at District Level to be implemented in all the 23 districts, for the formulation of District plans, monitoring, review and evaluation of the Plan Progrramme in the Districts. Under this scheme one post of Deputy Director (since predesignated as District Planning Officer) with supporting staff for each of the 23 districts in the State/ Three posts of Joint Directors in the Bureau of Economics and Statistics and three posts of Deputy Commissioners in the Office of the Commissioner of Panchayat Raj, with necessary supporting staff were sanctioned for further strengthening the District Planning Machinery in the Context of Constitution of District Planning Board for each district. All these posts have to be continued during the Seventh Plan period sharing the expenditure in the ratio of 50:50 between the State and the Centre. Amount of Rs225 lakhs is provided in the Seventh plan of which Es401nkhs in the Annual Plan 935-36.
Government of Andhra Pradesh Hyderabad
Finance & Planning Department
Keywords: Economic Services; Secretariat Economic Services; Economic Advice and Statistics; Weights and Measures; Stationery and Printing; Public Works Buildings; General Services; Physical Targets and Achievements; Centrally Sponsored Schemes; Development schemes/Projects; Outlay and expenditure; Special Component Plan Physical Targets.